The book of Isaiah personal impressions of Isaiah Berlin - Hardy, Henry 1949- (The Boydell Press, 2023)
This collection of pen-portraits of the renowned public intellectual Isaiah Berlin, published to mark the centenary of his birth, brings him vividly to life from many vantage points